Teknik Pembuatan Tulang dari Kertas dalam Make Up Karakter 3 Dimensi - Sofia Daniati; Qoirunisa Sekar Pratiwi; Agus Susanti; Widiati Alifah (Garina, 2024)
This research creates a technique of making paper bones in 3-dimension makeup character using materials that easy to find and affordable price. The methods used are literature, experiment, documentation, interview, questionnaire, and public test. Based on the results of feasibility tests of paper bone’s technique assessed by 6 validators on indicators of application effectiveness declared feasible, time efficiency indicators declared feasible, cost indicators declared very feasible, indicators of ease of discovery of materials declared very feasible. Based on the results of the feasibility test, the appearance of the effects of torn wounds using bones from paper assessed by 6 validators on indicators of wound composition was declared feasible, indicators of color combinations were declared feasible, indicators of similarity to the original wound were declared feasible, and indicators of detail were declared feasible. The results of the public test were conducted by 81 respondents. 96.3% said the wound effect similar to the original one. 100% said this technique affordable. 97.5% said this technique can be an alternative for 3-dimension makeup character cosmetic. 98.8% said this technique is easy to use by beginners. 100% said the ingredients are easy to find. 100% said paper bone can support zombie’s character appearance. 97.5% said interest with this technique. 98.8% said they like this technique. So can be concluded, this technique is worth to apply in 3-dimensional makeup character.